Identification of evolutionarily conserved regulators of muscle mitochondrial network organization. - Katti, P.; Ajayi, P.T.; Aponte, A.; Bleck, C.K.E.; Glancy, B. (Nature communications, 2022)
Mitochondrial networks provide coordinated energy distribution throughout muscle cells. However, pathways specifying mitochondrial networks are incompletely understood and it is unclear how they might affect contractile fiber-type. Here, we show that natural energetic demands placed on Drosophila melanogaster muscles yield native cell-types among which contractile and mitochondrial network-types are regulated differentially. Proteomic analyses of indirect flight, jump, and leg muscles, together with muscles misexpressing known fiber-type specification factor salm, identified transcription factors H15 and cut as potential mitochondrial network regulators. We demonstrate H15 operates downstream of salm regulating flight muscle contractile and mitochondrial network-type. Conversely, H15 regulates mitochondrial network configuration but not contractile type in jump and leg muscles. Further, we find that cut regulates salm expression in flight muscles and mitochondrial network configuration in leg muscles. These data indicate cell type-specific regulation of muscle mitochondrial network organization through evolutionarily conserved transcription factors cut, salm, and H15.